P261 Chemoprophylaxis for LTBI following mass screening in the workplace: unexpected outcomes in the over 35s. (12th November 2015) - Abunga, Y; Day, M; Williams, J; Mamo, JP; Brij, SO
Abstract : Introduction: In 2014, over 500 workers in a local factory were screened for TB. 3 cases of active pulmonary TB were identified and seen in the next weekly TB Clinic. 128 workers were identified for further assessment by the local TB Service, of whom 100 were found to be IGRA-reactive. This was declared a major incident and a TB Action Group was set up to facilitate additional out-of-hours TB clinics. Methods: The local CCG commissioned the additional TB clinics at standard respiratory out-patient tariff: approximately 35 workers were to be assessed by 5 TB clinicians in 2 weekly sessions (18:00–21:00 – 20 min slots) for the first 2 weeks, so that by week 3, all workers would be assessed. As in the weekly TB Clinic, the TB Pharmacy Team would be present to dispense TB medication with drug information leaflets and contact details. Chemoprophylaxis for LTBI was offered to all workers with reactive IGRA and no evidence of active TB independent of their age despite NICE guidance. Results: Of the 100 workers with reactive IGRA: 18 did not attend; 82 were offered chemoprophylaxis of whom 15 declined treatment; 67 started chemoprophylaxis of whom only 33 completed 3 months treatment with rifampicin and isoniazid. The rate of completion of chemoprophylaxis in the eligible group was 9/35 (25.7%) compared to 24/47 (51.1%) in the over 35 year olds. There was a transient rise in liver enzymes in 1 worker aged over 35 but otherwise there were no other significant side-effects. Discussion: It is difficult to deny chemoprophylaxis for LTBI infection on the basis of age in a large screening event such as this when the average age is 40 (range 17–63) and the oldest member of the cohort tolerated chemoprophylaxis without significant side-effects. The reasons for reluctance to continue chemoprophylaxis in this cohort are poorly understood although lifestyle issues such as reducing alcohol consumption were perceived to be barriers to successful completion of treatment. Conclusion: Chemoprophylaxis for LTBI in this cohort was not tolerated in the eligible population. When undertaking mass screening, it is important to ensure that non-standard treatment is funded, if this is to be offered. Treatment of the over 35s significantly increased the workload and cost of this cohort, although uptake of chemoprophylaxis and successful completion was twice that of the workers aged 35 or less.